Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/jcb.240450110
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger motif for single‐stranded nucleic acids? investigations by nuclear magnetic resonance

Abstract: Nuclear magnetic resonance (NMR) methods have been used to address issues regarding the relevance and feasibility of zinc binding to "zinc finger-like" sequences of the type C-X2-C-X4-H-X4-C [referred to as CCHC or retroviral-type (RT) zinc finger sequences]. One-dimensional (1D) NMR experiments with an 18-residue synthetic peptide containing the amino acid sequence of an HIV-1 RT-zinc finger domain (HIV1-F1) indicate that the sequences are capable of binding zinc tightly and stoichiometrically. 1H-113Cd spin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 38 publications
1
34
1
Order By: Relevance
“…CCHH zinc finger motif found widely in proteins that bind duplex DNA (Summers, 1991). The solution-state structure of the HIV-1 NC may be best described as a flexible polypeptide chain containing independently folded, noninteracting CCHC-type zinc finger domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCHH zinc finger motif found widely in proteins that bind duplex DNA (Summers, 1991). The solution-state structure of the HIV-1 NC may be best described as a flexible polypeptide chain containing independently folded, noninteracting CCHC-type zinc finger domains.…”
Section: Discussionmentioning
confidence: 99%
“…These findings, together with sitedirected mutagenesis (Gorelick et al, 1988;Meric & Goff, 1989) and structural results (Summers et al, 1990;South et al, 1991) provide what is now overwhelming evidence for the physiological relevance of the CCHC zinc finger motif in retroviruses. CCHC zinc finger sequences have been observed recently in nucleic acid binding proteins from Xenopus (Sato & Sargent, 1991) and humans (Rajavashisth et al, 1989) and may thus provide a generic structural motif for proteins that bind single-stranded nucleic acids (Summers, 1991).…”
Section: Hiv-i Nucleocapsid Proteinmentioning
confidence: 99%
“…CCHC-type zinc finger motifs have been found in one or two copies in the retroviral nucleocapsid proteins and their Gag precursors (19) and in proteins of plant viruses and of eukaryotic cells. It has been suggested that this type of zinc finger is involved in binding of single-stranded nucleic acids (20). UMSBP belongs to a distinct group of cellular proteins that contains several (5-9) adjacent CCHC motifs, including cellular nucleic acid binding protein (CNBP) from human and mouse, which binds a G-rich single-stranded sequence of a sterol regulatory element (21); hexamer binding protein (HEXBP) from Leishmania major, which binds a G-rich singlestranded repeated sequence found in the 5Ј-untranslated region of the gene encoding GP63 (22); byr3 from Schizosacharomyces pombe (23); and CnjB from Tetrahymena thermophila (24).…”
mentioning
confidence: 99%
“…1 A and C), distinguish glh-i from other known RNA helicases. The zinc fingers are of the CC/HC type found in the retroviral NBPs and the CNBP, the former of which has been shown to bind Zn2+, viral genomic RNA, and coding-strand DNA (30,33,34). The presence of this type of zinc finger motif further predicts that the glh-1 protein interacts with a single-stranded nucleic acid, possibly an RNA or population of RNAs.…”
Section: Resultsmentioning
confidence: 99%